Pelaksanaan Pembelajaran Tematik di Kelas V di Madrasah Ibtidaiyah Negeri (MIN) 1 Kabupaten Kubu Raya - Salito (Jurnal Pendidikan Dasar Islam, 2023)
This study aims to determine; 1) planning thematic learning, 2) implementing thematic learning, 3) inhibiting and supporting factors in thematic learning. This study used a qualitative method with a descriptive qualitative approach, with data analysis techniques using data reduction, conclusions. Primary data source; class teachers and students. While the secondary uses research journals, books and websites. Data collection techniques using; observation, interview and documentation. The results of the research show that the planning carried out by the Thematic teachers in Class V chose a learning design, which was included in the making of the Lesson Implementation Plan (RPP) also used methods, media and strategies, in the learning process, learning according to the indicators to be achieved. Implementation of teacher learning uses learning methods, namely, lecture methods, discussions, question and answer, and assignments, also the strategies used vary according to the characteristics of the subjects or sub-themes of thematic learning also use learning media in accordance with the sub t such as media pictures, power point, blackboard and bicycle. Internal and external factors, internal factors in learning come from the students themselves who do not understand the material or themes conveyed by the teacher towards thematic learning. External inhibiting factors are seen from the environment where students live which cannot provide motivation and enthusiasm to students, so that students go to school there is no motivation to learn. While the supporting factors in the learning process are strongly influenced by the existence of a comfortable and pleasant classroom climate, there are also learning media available in the classroom so that the teacher can explain easily.